Gestalt therapy history, theory, and practice - Woldt, Ansel L.; Toman, Sarah M. (Thousand Oaks, Calif. ; London : SAGE, 2005)
Introducing the historical underpinnings & fundamental concepts of Gestalt therapy, this volume takes both a conceptual & a practical approach to the examination of classic & cutting-edge constructs.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Gestalt therapy